Advertising investment under switching costs. Issue 1 (1st January 2021) - Cui, Ting; Wang, Chan; Nie, Pu-yan
Abstract: Switching costs are exceedingly important in service industries including platform firms and IT firms, and, have a strong effect on firms' advertising investments and market structure. This study examines the effects of switching costs on advertising using a two-stage discrete-time dynamic duopoly model. Firstly, we argue that switching costs reduce firms' advertising investments. Secondly, both brand stealing effects and brand expansion effects of advertising promote firms' competition regarding pricing and advertising investments. Finally, firms with high prices invest more in advertising thank others. Because of switching costs, firms compete in terms of both price and advertising investment. This article captures the relationship between switching costs and advertising investments in detail. The managerial policy is that firms to determine advertising investment should consider switching costs.